Dramaturgia em movimento: tendências poéticas no teatro de animação dos grupos Giramundo e Catibrum - Júlio, Larissa Miranda (2011)
This study begins the search for an understanding of dramaturgy for the puppet theater. Based on the recognition of the specificities of this category of theater, it is realized that literary dramaturgy does not include all the needs of discursive techniques used by this form of spectacle. Considering the relationship between the actor and the puppet, the physical aspects of the puppet, the manipulation techinic, used, among others aspects. The contemporary conception of dramaturgy ends up being the best that will encompass the movement of theatricality in which the current puppet theater is inserted. For a more detailed analysis of how this dramaturgy can be built, these shows were surveyed: Pinocchio, of the Giramundo group, and O cavaleiro da triste figura, of the Catibrum group. The poetic proposals of these two groups from Belo Horizonte are similar and are distinguished by a series of issues, but serve as examples of ways to use the dramaturgy of puppet theater in Brazil today.